Children's grief: repertoires of practices in institutional early childhood education and care. (3rd July 2022) - Lipponen, Lasse; Pursi, Annukka
ABSTRACT: Although grief is common in children's lives, it is under-researched and undertheorized. The aim of our study is to investigate children's grief as a cultural activity that consists of repertoires of practices in institutional early childhood education and care (ECEC). ECEC is a central site where grief is learned and practiced. Taking a cultural-historical approach using ethnographically inspired research methods, we analyzed interaction in the contexts of separation, absence of a parent, and social exclusion. We focused on the moments of grief, demonstrating how children and adults organize their social encounters and interactional history, and engage in rich repertoires of practices. We discuss the conditions for recognizing grief in institutional ECEC.